SEMDSA/ACE-SA Guideline for the Management of Hypothyroidism in Adults - Joel A. Dave; Ania Klisiewicz; Zaheer Bayat; Nazeer Ahmed Mohamed; Zane Stevens; Tanya Kinvig (South African Family Practice)
Background: Hypothyroidism is a common clinical condition confronting all healthcare practitioners yet there remains uncertainty about the optimal medication and optimum treatment targets. In addition, many patients remain symptomatic despite using recommended medications and attaining recommended treatment targets.